A Rare Case of Huge Gastric Adenoma Composed of Pyloric Gland Adenoma and Foveolar-Type Adenoma with Serrated Dysplasia Cured by Endoscopic Submucosal Dissection - Han, Shuai; Yin, Shouxin; Sun, Zongguo; Ren, Shuangshuang; Wei, Zhi (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Han S, Yin S, Sun Z, Ren S, Wei Z. A rare case of huge gastric adenoma composed of pyloric gland adenoma and foveolar-type adenoma with serrated dysplasia cured by endoscopic submucosal dissection. Turk J Gastroenterol. 2025;36(8):537-539.